Smart Village sebagai Upaya Penguatan Kapasitas Pemerintahan Nagari - Kusdarini Kusdarini; Desna Aromatica; Ria Ariany; Hendri Koeswara; Muhammad Ichsan Kabullah; Misnar Sitriwanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2020)
The existence of the Nagari Government as the foremost government is expected to improve the welfare of the community. In 2016 the poverty rate in Solok Regency reached 10% of the total population of 363,684 people, where this poverty was caused by food poverty. Even though in 2017 the poverty rate decreased, poverty remains high. For this purpose, this community service activity aims to introduce innovative concepts in managing the nagari government so as to produce a module that can become a blueprint for a governance concept in the concept of smart villages. These two adjacent Nagari can support each other and become a pioneer for other nagari, especially the advanced nagari to rise at the Village level or Nagari with an independent village index. This activity cover several things, namely 1) Introduction of the concept of smart rural. 2) Identification of smart rural dimensions that have developed and need to be developed. The result of this activity was that in Nagari Selayo and Nagari Koto Baru, Kubung District is preparing to go to the smart village. There are still many steps that need to be done, especially related to the readiness of human resources and also Nagari Government institutions and also community participation. Because the key to the success of the realization of smart villages is the active involvement of all elements involved, with the support of qualified information technology (ICT).